Ulnar Nerve Neuropathy after Distal Radius Fracture Malunion. Uncommon Intra-Operative Findings and a Review of the Literature - Athanaselis, Efstratios D.; Papageorgiou, Fotios; Deligeorgis, Dimitrios; Malizos, Konstantinos N.; Varitimidis, Sokratis E. (International Journal of Innovative Research in Medical Science, 2020)
Distal radius fractures are among the most common fractures. Though associated neurologic problems are not uncommon, ulnar nerve dysfunction is a rare complication. An interesting case of sensory impairment of the ulnar nerve in a female patient with distal radius malunion, 6 months after a conservatively treated fracture, in which surgical intervention revealed an anatomic variation of ulnar nerve route, is presented in conjunction with a review of relevant literature.